Students Evaluation on Factors Affecting Effective Teaching in Science Field of Assumption University - Teeranusoun, Tawatchai (Scholar: Human Sciences, 2014)
To be a good teacher, one has to have a lot of knowledge, good communication with all people, good attitude, and good teaching. The objectives of this study were: (1) To find the average scores of students’ evaluation on factors affecting effective teaching in science filed of A.U., (2) To find out the factors of affecting effective teaching method. The population for this study was all students for first semester of 2012, those who were in science field of A.U. The sample was composed of 440 students during 16, July 2012 to 31, August 2012. The survey and convenience sampling technique research method were used in data collection. The highest score of finding was “Teachers come to the class on time with the mean and Sd. (7.9034, 1.4595)”.The lowest score was “Teacher explain how to apply this subject in the real world with the mean and Sd. (7.0920, 1.4469)”, and overall for Evaluation of effective teaching with the mean and Sd. (7.6641, 1.1551). All factors effective teaching was high rating (1: low to 10: high). Factor analysis generated two main factors: (1) Teaching performance, (2) Course Content and Communication. The first main factor consisted of 11 items. They were: “Teachers are enthusiastic in teaching.”, “Teachers are able to motivate students to study, to think.”, “Teachers have good personality.”, “Teachers have expertise in the subject being taught.”, “Teachers have been well-prepared for the class.”, “Teachers provide clear explanations on important issues.”, “Teachers show their professional competence in the subjects.”, “Teachers are able to teach and explain clearly.”, “I understand what the teachers teach.”, “Teachers demonstrate good role models for young people.” and “Teachers are effective in teaching that subjects.”. The second main factor consisted of 5 items. They were: “Course objectives and contents are explained clearly.”, “Teachers explain how to apply this subject in the real world.”, “Teachers explain how this subject relates to the other subjects.”, “Teachers inform when student have some problems.”, and “Teachers explain the value of morality and ethics in class.”. Pearson’s correlation (0.723) showed that high correlation of two main factors with overall Evaluation of Teaching Effectiveness. Regression analysis showed that two main factors had positive effect on overall for Evaluation of Teaching Effectiveness. It showed that teaching performance had good effect followed by course content and communication factor. The study provided more understanding additional factors that may affect goals of effective teaching, which may help Assumption University, become high quality.